Coagulase-negative staphylococcal prosthetic valve endocarditis—a contemporary update based on the International Collaboration on Endocarditis: prospective cohort study. Issue 7 (24th October 2008) - Chu, V H; Miro, J M; Hoen, B; Cabell, C H; Pappas, P A; Jones, P; Stryjewski, M E; Anguera, I; Braun, S; Muñoz, P; Commerford, P; Tornos, P; et al.
Abstract : Objective: To describe the contemporary features of coagulase-negative staphylococcal (CoNS) prosthetic valve endocarditis (PVE). Design: Observational study of prospectively collected data from a multinational cohort of patients with infective endocarditis. Patients with CoNS PVE were compared to patients with Staphylococcus aureus and viridans streptococcal (VGS) PVE. Setting: The International Collaboration on Endocarditis-Prospective Cohort Study (ICE-PCS) is a contemporary cohort of patients with infective endocarditis from 61 centres in 28 countries. Patients: Adult patients in the ICE-PCS with definite PVE and no history of injecting drug use from June 2000 to August 2005 were included. Interventions: None. Main outcome measures: Heart failure, intracardiac abscess, death. Results: CoNS caused 16% (n = 86) of 537 cases of definite non-injecting drug use-associated PVE. Nearly one-half (n = 33/69, 48%) of patients with CoNS PVE presented between 60 days and 365 days of valve implantation. The rate of intracardiac abscess was significantly higher in patients with CoNS PVE (38%) than in patients with either S aureus (23%, p = 0.03) or VGS (20%, p = 0.05) PVE. The rate of abscess was particularly high in early (50%) and intermediate (52%) CoNS PVE. In-hospital mortality was 24% for CoNS PVE, 36% for S aureus PVE (p = 0.09) and 9.1% for VGS PVE (p = 0.08). Meticillin resistance was present in 68% of CoNS strains. Conclusions: Nearly one-half of CoNS PVE cases occur between 60 days and 365 days of prosthetic valve implantation. CoNS PVE is associated with a high rate of meticillin resistance and significant valvular complications.